Wide eksisi dan flap rhomboid pada karsinoma basal sel regio facial - Kadek Nopy Arianti; Made Oka Sastrawan; Fatur Reyhan Muradi; Muhammad Aflah; Casvin Jus (DiscoverSys Inc., 2022)
Background: Basal cell carcinoma is one of the most common classifications of non-melanoma skin cancer (75% - 80%) of all cancers. Basal cell carcinoma causes widespread local destruction including soft tissue, cartilage, and bone, thus impairing function and aesthetics, especially for the facial area. One of the most common reconstructive techniques for Basal Cell Carcinoma is the Rhomboid flap. This case report aims to report the use of the rhomboid flap reconstruction technique in post-wide excision of basal cell carcinoma. Case Description: A man, 54 years old, ethnic Balinese, came to the General Surgery Clinic of RSUD Klungkung with a complaint that a mole on the patient's left eye appeared enlarged with itching and bleeds easily. These complaints began to be felt since about 2 weeks before entering the hospital. Initially the patient's mole had been there for 5 years, previously the patient had no complaints about the mole, the initial lesion was in the form of a small brownish lump which was then felt to be getting bigger with itching and bleeding easily. The patient did not complain of pain. Examination of the localized status on the lateral periorbital sinistra showed blackish nodules with hyperpigmented macules, solitary, 2cm x 1cm in size, visible erosions, well-defined borders, irregular shape. Conclusion: The provisional diagnosis of Suspected Malignant Skin Tumor was established based on history, physical examination, with management therapy wide excision and reconstruction with Rhomboid Flap followed with biopsy. Latar Belakang : Karsinoma Sel Basal (KSB) adalah salah satu kanker kulit yang paling sering ditemukan dari seluruh kanker kulit non melanoma. Karsinoma Sel Basal dapat mengakibatkan kerusakan local dengan infiltrasi yang luas sehingga mengganggu fungsi dan estetika, terutama untuk daerah wajah. Salah satu pilihan teknik rekonstruksi yang bisa dilakukan pada Karsinoma Sel Basal di regio wajah adalah Rhomboid flap. Laporan kasus ini bertujuan untuk melaporkan penggunaan tehnik rekonstruksi dengan flap rhomboid pada pasca eksisi luas pada karsinoma sel basal. Deskripsi Kasus: Seorang laki-laki, 54 tahun, suku Bali, datang ke Poliklinik bedah Umum RSUD Klungkung dengan keluhan tahi lalat pada sebelah mata kiri pasien tampak membesar disertai gatal dan mudah berdarah. Keluhan tersebut mulai dirasakan sejak sekitar 2 minggu sebelum masuk RS. Awalnya tahi lalat pasien sudah ada sejak 5 tahun yang lalu, sebelumnya pasien tidak ada keluhan pada tahi lalat tesebut, lesi awal berupa benjolan kecil berwarna kecoklatan yang kemudian makin lama dirasakan makin membesar disertai rasa gatal dan mudah berdarah. Keluhan nyeri tidak dikeluhkan oleh pasien. Pemeriksaan status lokalis pada periorbital lateral S tampak nodul kehitaman disertai makula hiperpigmentasi, soliter, ukuran 2cm x 1cm, tampak erosi, batas tegas, bentuk tidak beraturan. Kesimpulan: Diagnosis sementara Tumor Kulit Suspek Malignant ditegakkan berdasarkan anamnesis, pemeriksaan fisik dengan terapi eksisi luas + biopsi + rekonstruksi dengan Rhomboid Flap.